1984
DOI: 10.1111/j.1744-7348.1984.tb03057.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction and the growth of vining peas

Abstract: SUMMARYThe effects of differing soil conditions at two sites on the growth of vining peas are described. The work was carried out over several seasons having contrasting rainfall at the time of crop emergence.Topsoil compaction induced by tractor wheelings reduced plant population and yield of vining peas by up to 70%. On the compacted plots peas were unable to compensate for the low population which was demonstrated by the inclusion of a non‐compacted treatment thinned to the same population as the compacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previous workers have shown that reduced plant population and reduced performance of plants are both important factors whereby soil compaction can affect growth and yield of several crops (Hebblethwaite & McGowan, 1980;Dawkins et al, 1984). The principal aim of this study was to examine to what extent restricted growth and yield of crops grown in compacted soil could be related to impaired light interception or to impaired conversion coefficients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous workers have shown that reduced plant population and reduced performance of plants are both important factors whereby soil compaction can affect growth and yield of several crops (Hebblethwaite & McGowan, 1980;Dawkins et al, 1984). The principal aim of this study was to examine to what extent restricted growth and yield of crops grown in compacted soil could be related to impaired light interception or to impaired conversion coefficients.…”
Section: Discussionmentioning
confidence: 97%
“…deformed and distorted roots, shorter internodes, increased stem diameter etc. has led to suggestions that plant responses to soil compaction may be influenced by mechanisms other than impaired nutrient and water capture (Dawkins, Hebblethwaite & McGowan, 1984;Brereton, 1986) and some workers have speculated on the possible role of hormonal 'signals' between root and shoot systems (Brereton, McGowan & Dawkins, 1986;Masle & Passioura, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…For example, compaction enhances seed–soil contact, improving germination and crop establishment (Radford & Nielsen, ), and it can increase crop yields in dry years (Namdari et al ., ). By contrast, a wide range of studies have reported reductions in crop yield as a result of soil compaction (Raghavan et al ., ; Negi et al ., ; Dawkins et al ., ; Radford et al ., ; Botta et al ., ; Chamen et al, ; Abu‐Hamdeh, ; McKyes et al ., ; Mamman et al ., ). Soil compaction increases soil specific resistance (Canarache, ) which, in turn, increases draft and implement wear (Godwin & Spoor, ).…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, the soil is often not dry enough for good seedbed preparation and sowing (Le Bail and Meynard, 2003). Pea is sensitive to dense soil (Dore´, 1992), which decreases growth, nitrogen nutrition and crop yield in field conditions (Crozat et al, 1992;Dawkins et al, 1984). As soil water content is generally lower during the sowing period in the autumn than in the spring, soil structure would be expected to be more favourable for winter pea crops than for spring pea crops.…”
Section: Introductionmentioning
confidence: 99%